Priniciples of engineering analysis - Sinha, Amritasu (Alpha Science International, 2012)
This book explains Signals and Systems. It offers different transformation techniques such as Laplace, Fourier and Z transforms mathematically and subsequently its applications in solving differential and integral equations are also given.